DAMPAK PEMBAYARAN ZAKAT TERHADAP PERILAKU KONSUMSI PEGAWAI NEGERI SIPIL DI DEPARTEMEN AGAMA KOTA SURABAYA - Aris Kurniawan Ridho; Sri Herianingrum (Universitas Airlangga, 2019)
The objective of this study is to find out how the impact of Paying Zakat on consumptive behavior of civil servants in the Department of Religion of Surabaya. The research used qualitative descriptive case study method. The data used were primary and secondary data. The primary data was obtained from the results of interview, observation, and documentation on the relevant parties, while secondary data was obtained through printed media, electronic media as well the Internet on consumptive behavior, in addition to supporting data from various journals and books which are relevant to this study. The results of the research show that zakat gives impact on consumptive behavior of Civil Servants of the Department of Religion in Surabaya. When their salary is deducted in accordance with the provisions of zakat, they feel that the consumptive behavior to fulfill their daily needs is somewhat different when they pay zakat. The efficiency of zakat payment or zakat collection is one of their reasons to continue paying their zakat in accordance with existing provisions. Among the greatest benefits they perceived is the increasing awareness of the obligation to pay zakat and applying consumption principles in accordance to the Islamic norms.Keywords: zakat, consumptive behavior in IslamREFFERENCESAd Dimasyqi, Taqiyyuddin. 2005. Kifayah al Akhyar. Beirut: Darul Kutub Al ‘Ilmiah.Al Gazali, 1994. Rahasia Puasa dan Zakat.Bandung: Penerbit Karisma.Al Qurthubi, Abi Abdillah Muhammad ibn Ahmad. 2006. Tafrir Ahkam al Qur’an. Beirut: Al-Resalah Publishers.Az Zuhaili, Wahbah. 1985. Fiqh Al-Islamiy wa Adillatuhu. Damaskus: Dar al Fikr.Aziz, Muhammad dan Shalikhah. 2014. Zakat Profesi dalam Perspektif Undang-Undang no. 22 Tahun 2011 dan Hukum Islam. Jurnal Ulul Albab Vol. 15, No. 2.Hafiduddin, Didin2004. Zakat dalamPerekonomian Modern. Jakarta: Gema Insani.Hidayat, Ahmad. 2015. Manajemen Zakat dan Perilaku Konsumsi Mustahik. Jurnal Banking and Management Review, Vol. 4, No. 2.Mariana, Hanik. 2016. Korelasi Zakat dengan Periaku Konsumen dan Pemberdayaan Ekonomi Masyarakat di Banyudono, Ponorogo. Jurnal Muslim Heritage Vol. 1, No. 1.P3EI, 2010.Rasyid, Sulaiman. 1994. Fiqh Islam. Bandung: Sinar Baru Algesindo.Rosmiati, Nur. 2012. Studi Analisis Pengelolaan Dana Zakat Dalam Mengentaskan Kemiskinan. Makasar: UIN Alaudin.Sudirman. 2007. Zakat dalam Pusaran Arus Modernitas. Malang: UIN Malang Press.Al Faizin, Abdul Wahid & Sri Herianingrum. 2018. Zakat: Concept and Implications to Social and Economic (Economic Tafsir of Al- Tawbah: 103). Journal of Islamic Monetary Economic and Finance Vol. 4, No. 1.Yasin, Ahmad Hadi. 2012. Panduan Zakat Praktis. Jakarta: Dompet Dhuafa Republika.